Gambaran Kestabilan Emosi dan Perilaku Agresif Siswa Kelas IV-VI Di SDS Islam Plus “X” - Intan Andryani; Purwanti Margaretha (Provitae: Jurnal Psikologi Pendidikan, 2021)
Pre-adolescent or pre-puberty phase is a transitions phase from childhood to becoming an adolescent. This phase is the most vulnerable phase in the development of school-aged children because children will experience many changes, either for physically or psychologically. One of the changes that stands out is change in emotion that occurs due to hormonal changes, which affect the emotional states so that individuals have moods that are volatile or unstable. One of behavior that can arise due to this unstable emotion is aggressive behavior. This research is using quantitative method to see the depiction of Student's emotional stability and aggressive behavior. The participant is gathered using convenience sampling of 162 students aged 10 to 12 years old at Islamic Elementary School Plus X. Results are showing that the majority of the participants are having mild emotional stability, but there are 43 students (26%) that are having low emotional stability. Majority of the participant also having a mild aggressive behavior and there are 34 students (21%) that are having high aggressive behavior. Furthermore, research shows that there is a significant negative correlation between emotional stability and aggressive behavior (r=0.378; p=0.00 < 0.05). Therefore, efforts are needed to increase the student's emotional stability so that it can minimize the aggresive behavior at school. Researcher plans to carry out an intervention plan that are provided in form of group guidance with role play methods to the research participants.